Report of the PPP Sub-Group on Social Sector Public Private Partnership - Planning Commission (Planning Commission, 2004)
Most of these services have been traditionally provided through in-house facilities of governments, financed and managed directly by them. Public-private- partnership (PPP), on the other hand, is an approach under which services are delivered by the private sector (non-profit/for-profit organizations) while the responsibility for providing the service rests with the government. This arrangement requires the government to either enter into a comment with the private partner or pay for the services {reimburse) rendered by the private sector. Contracting prompts a new activity, especially so, when neither the public sector nor the private sector existed to provide the service.
Government of India Planning Commission
Government of India Planning Commission